Effects of black soybean powder particle size on the characteristics of mixed powder and wheat flour dough. (15th September 2022) - Yang, Liping; Wang, Sunyan; Zhang, Houfang; Du, Chuanlai; Li, Songnan; Yang, Jianting
Abstract: In this study, black soybean powders of five different particles sizes (coarse, regular, fine, very fine, and superfine) were prepared and mixed with wheat flour to evaluate the effects of particles sizes on the characteristics of mixed powders prepared with black soybean powders and wheat flour, and the dough prepared from these mixed powders. The black soybean powder was rich in ash, protein, lipid, and fiber, especially the superfine black soybean powder, which had the highest lipid (26.85%) and fiber (13.12%) content. Compared to wheat flour, the addition of black soybean powders altered the water retention capacity (WRC), lactic acid capacity, and oil binding capacity (OBC) of mix powders; superfine black soybean powder had the lowest WRC and OBC (0.76 and 0.95 g/g, respectively). The digestibility was significantly affected by black soybean powder particle size. Larger particles tended to result in higher resistant starch content. The water absorption of dough was independent of particle size, and the particle size significantly altered the stability time, development time, pasting and viscoelastic properties, and secondary structure of the dough. Determination of the disulfide bond content and scanning electron microscopy of dough revealed that dough prepared from black soybean flour of large particle sizes had a more stable gluten structure. Highlights: Black soybean powders of five different particles sizes were prepared. The effect of particle size on mix powder and dough characteristics was studied. The influence of particle size was revealed based on structure and properties. Provided reference for the development of functional food with black soybean.